Analysis of the Effectiveness, Efficiency and Contribution of Regional Taxes to Regional Original Income in Sub-Regional Provincies Riau Period 2019-2023 - Jhon Raphael Saragih; Yusnaini Yusnaini; Charlene Charlene (Digital Innovation : International Journal of Management, 2024)
The aim of this research is to analyze the level of effectiveness, efficiency and contribution of regional taxes to Original Regional Income in the sub-region of Riau province for the 2019-2023 period. The data collection technique used is secondary data in the form of financial reports for the 2019-2023 period at the financial djpk. The sample in this study was taken from financial reports registered on the website https://djpk.kemenkeu.go.id/portal/data/apbd. So the data obtained was 12 sub-regions x 5 years = 120 data. The data will be analyzed using quantitative methods. The research results show that the level of effectiveness in the sub-region of Riau province is classified as effective with a percentage of 93%. The level of efficiency in the sub-region of Riau province is classified as inefficient with a percentage of 102%. The level of regional tax contribution in the sub-region of Riau province is quite good with a percentage of 43%.